Empowering the Future: Innovative Education Strategies for Global Skills in the Context of the Golden Generation 2045 - Syahriani, Fadilla; Yufriadi, Ferdi; Fismanelly (MultiTech Publisher, 2023)
This research aims to explore the development of 21st century skills in a global context for the 2045 generation through innovative educational strategies. The study used descriptive qualitative research methods and included in-depth interviews with teachers, classroom observations and document analyses. The uniqueness of this study lies in the comprehensive mapping of the implementation of innovative strategies in a multicultural and international education environment. The results of this study highlight the success of student-centred learning approaches, integration of advanced technologies and curriculum design linked to 21st century skills. These findings contribute significantly to a deeper understanding of how innovative education can address the global challenges of the 2045 generation. In addition, this research provides a concrete picture of the dynamics and success of implementing this strategy in an international context. The novelty of this research lies in the combination of a qualitative descriptive approach and global impact, which makes a valuable contribution to the textbook literature. The practical implications of this research include specific guidelines for policy makers, administrators and education professionals who want to prepare students for a challenging future in the globalised era of 2045.